2010
DOI: 10.1590/s0102-695x2010000400003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos parâmetros hematológicos e bioquímicos de ratas no segundo terço da gestação submetidas à ação do extrato metanólico de Cereus jamacaru DC., Cactaceae

Abstract: RESUMO:Os efeitos da administração oral do extrato metanólico (EM) de Cereus jamacaru DC., Cactaceae, foram investigados sobre os parâmetros hematológicos e bioquímicos em ratas Wistar adultas grávidas. Vinte ratas (n = 5 por grupo) foram tratadas durante quatro dias consecutivos com EM por via oral nas doses de 100, 250 e 500 mg/kg de peso e, em seguida, determinados os perfis bioquímico e hematológico. Os resultados mostraram que durante o período do tratamento não foi observado efeitos nocivos ou óbitos. Os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
1
7
0
3
Order By: Relevance
“…Clinical biochemicals parameters were analyzed as described early (Messias et al, 2010). The parameters measured with an automated biochemical analyzer (BIOPLUS 2000) were total protein (TP), albumin (Alb), total bilirubin (T. Bil), aspartate aminotransferase (AST), alanine aminotransferase (ALT), γ-glutamil transferase (GGT), total cholesterol (TC), urea, creatinine (Cr), and glucose.…”
Section: Hematological and Clinical Biochemistrymentioning
confidence: 99%
“…Clinical biochemicals parameters were analyzed as described early (Messias et al, 2010). The parameters measured with an automated biochemical analyzer (BIOPLUS 2000) were total protein (TP), albumin (Alb), total bilirubin (T. Bil), aspartate aminotransferase (AST), alanine aminotransferase (ALT), γ-glutamil transferase (GGT), total cholesterol (TC), urea, creatinine (Cr), and glucose.…”
Section: Hematological and Clinical Biochemistrymentioning
confidence: 99%
“…O mandacaru, é um cacto colunar, característico da região semiárida do Brasil (ROCHA; AGRA, 2002), apresentando uma série de usos nessa região, como para a construção (LORENZI; MATOS, 2002), forragem para os animais (LUCENA et al, 2015), sendo também de grande importância medicinal, havendo relatos de usos de diversas partes da planta, como as raízes (ANDRADE, MARQUES e ZAPPI, 2006), o caule (MESSIAS et al, 2010), as flores (GONZÁLES-HERNÁNDEZ; VILLARREAL 2007), como também o fruto (SILVA; ALVES, 2009;NUNES et al, 2013).…”
Section: Introductionunclassified
“…Messias et al (2009) also reported these differences when rat blood was analyzed using a hematology analyzer for humans compared to the hemocytometer. The values obtained in both automated methods compared with the manual count, even with low values, are consistent with values usually found for rats (Harkness;Wagner., 1993;Cubas et al, 2007;Messias et al, 2009;2010;Melo et al, 2012;Lima et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To perform the blood collection rats with 12 hours of fasting were anesthetized according to Messias et al (2009;2010), with ketamine 85mg/kg (Vetbrands®) and xylazine 3mg / ml (Vetbrands®), and immobilized. Afterwards, 1 ml of blood was collected by cardiac puncture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation